Quantifying rapid changes in cardiovascular state with a moving ensemble average. (3rd October 2017) - Cieslak, Matthew; Ryan, William S.; Babenko, Viktoriya; Erro, Hannah; Rathbun, Zoe M.; Meiring, Wendy; Kelsey, Robert M.; Blascovich, Jim; Grafton, Scott T.
Abstract: MEAP, the moving ensemble analysis pipeline, is a new open‐source tool designed to perform multisubject preprocessing and analysis of cardiovascular data, including electrocardiogram (ECG), impedance cardiogram (ICG), and continuous blood pressure (BP). In addition to traditional ensemble averaging, MEAP implements a moving ensemble averaging method that allows for the continuous estimation of indices related to cardiovascular state, including cardiac output, preejection period, heart rate variability, and total peripheral resistance, among others. Here, we define the moving ensemble technique mathematically, highlighting its differences from fixed‐window ensemble averaging. We describe MEAP's interface and features for signal processing, artifact correction, and cardiovascular‐based fMRI analysis. We demonstrate the accuracy of MEAP's novel B point detection algorithm on a large collection of hand‐labeled ICG waveforms. As a proof of concept, two subjects completed a series of four physical and cognitive tasks (cold pressor, Valsalva maneuver, video game, random dot kinetogram) on 3 separate days while ECG, ICG, and BP were recorded. Critically, the moving ensemble method reliably captures the rapid cyclical cardiovascular changes related to the baroreflex during the Valsalva maneuver and the classic cold pressor response. Cardiovascular measures were seen to vary considerably within repetitions of the same cognitive task for each individual, suggesting that a carefully designed paradigm could be used to capture fast‐acting event‐related changes in cardiovascular state.